Understanding the energetic costs of living in saline environments: effects of salinity on basal metabolic rate, body mass and daily energy consumption of a long-distance migratory shorebird - Sánchez Gutiérrez, Jorge; Masero Osorio, José Antonio; Abad Gómez-Pantoja, José María; Villegas Sánchez, María Auxiliadora; Sánchez Guzmán, Juan Manuel (Journal of Experimental Biology, 2011)
Many migratory vertebrates typically move between habitats with varying salinities during the annual cycle. These organisms clearly exhibit a remarkable phenotypic flexibility in their ‘osmoregulatory machinery’, but the metabolic consequences of salinity acclimatization are still not well understood. We investigated the effects of salinity on basal metabolic rate (BMR), body mass and daily energy consumption of a long-distance migratory shorebird, the dunlin (Calidris alpina), outside the breeding season. Mass-corrected BMR and daily energy consumption increased significantly by 17 and 20% between freshwater (0.3‰ NaCl) and saltwater (33.0–35.0‰ NaCl), respectively. Body mass in both captive and wild dunlins was lower (9–16%) in saline than in freshwater environments. These changes on BMR and body mass were quickly reversed by returning the birds to freshwater, suggesting that metabolic adjustment to saltwater and metabolic readjustment to freshwater are both processes that occur in a few days. Our findings support empirically that the processes of developing and maintaining an active osmoregulatory machinery are energetically expensive, and they could help to explain diet and/or habitat selection patterns along the flyway. Finally, we discuss whether body mass loss in saltwater may be a strategy to reduce maintenance cost in osmotically stressful conditions such as overwintering in marine habitats, and raise some methodological implications for studies of BMR-related outcomes using captive birds captured in saline environments. The project CGL2006-01227 (Spanish Ministry of Science) provided financial support for this study. J.S.G. was the beneficiary of a grant from the Junta de Extremadura. peerReviewed